Impact of Fukushima nuclear disaster on oil-consuming sectors of Japan - Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Ehsan Rasoulinezhad (Asian Development Bank Institute (ADBI), 2017)
The Fukushima Daiichi nuclear disaster was an accident at the Fukushima I Nuclear Power Plant in Fukushima, Japan, which resulted primarily from the tsunami following the Tohoku earthquake on 11 March 2011, and which led to year-long nuclear shutdown in the country. During the shutdown, Japan substituted fossil fuels for nuclear power and became more dependent on import and consumption of fossil fuels including oil, gas, and coal. In this paper, we try to shed light on the elasticity of oil consumption to crude oil price before and after the Fukushima disaster in Japan's various economic sectors. To do so, we apply a cointegration analysis and perform a vector error correction (VEC) variance decomposition by using quarterly data in two separate subperiods from Q1 1981 to Q4 2010 and from Q1 2011 to Q4 2015. Our findings reveal that the absolute value of elasticities of oil consumption by some economic sectors, such as the industry, non-energy, and transportation sectors to oil prices, has reduced after the disaster because of increased dependency on oil consumption, which endangered energy security in the country. To raise energy self-dependency and energy security, Japan needs to diversify its energy supply resources. For instance, the share of renewable energy in Japan's energy basket needs to increase. Because renewable energy projects are mainly considered risky and banks are reluctant to finance them, we introduce an innovative form of financing these projects: Hometown Investment Trust Funds, which has been introduced and applied in Japan and other parts of Asia.
Keywords: C32; O49; Q43; 330; Economics; Energy; Japan